Kewenangan Notaris dalam Membuat Akta Roya Hak Tanggungan - Yusuf Bagus Purnama (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2018)
Akta roya mortgages rights are usually made by the Land Office which indicates that the creditor's receivable has been paid or the certificate of liability is removed because it has been deleted. However, because the certificate of mortgage that is controlled by creditors is lost, then in the case of the right of liability delete can not be deleted in the certificate of mortgage. In this case the creditor requires a notarize deed of notarial deed or notarized deed or deed made by a notary. Akta roya hak tanggungan is one of the authentic deeds made by a notary at the request of the creditor as the party containing the statement of the creditor that the certificate of debtor's right of debt in his power has been lost. The existence of notarial deeds within the scope of the mortgage rights has not been explicitly regulated in UUJN, UUHT and other regulations, but the notary may make this deed based on the authority of a notary as meant in Article 15 paragraph (1) UUJN. In that provision there is a blurred norm regarding the authority of a notary to create a deed of the rights of the dependent. The issues raised in this research are about the authority of a notary to make deed roya mortgages, and position aka roya mortgages made by a notary. The results of this study indicate that in general the notary has the authority to make a notarial deed in the form of the deed of the right of the death based on Article 15 paragraph (1) UUJN, as long as there is no other rule more specifically regulate it. Akta roya hak tanggungan is a notarial deed which has a position as a substitute of the missing mortgage certificate, which functions as a requirement of registration of roya or write off of dependent righ